Kinematic Modelling of Multi-Terrain Pine Needle Collecting Robot (PiNCoR) for the Hilly areas of Uttarakhand - Shival Dubey; Manish Prateek; Mukesh Saxena (Institute of Advanced Engineering and Science, 2015)
Uttarakhand – a northern state of India in the foothills of Himalayas has approximately 64.8% of forest. Pine (Pinus roxburghii) is an important tree species which is because of its numerous uses becomes more prominent in this hilly state. Pine Needle Collecting Robot (PiNCoR) is a machine designed to collect pine needles from the high altitude pine forest regions. The robot is capable to maneuver over rough terrains, can navigate through craters and can stock the collected pine needles. After analyzing the design constraints for navigation on the hilly terrains, a small rover was designed and the kinematics portion is discussed in this paper. With the use of a versatile rocker bogie suspension mechanism, this paper also presents the kinematic modelling of a wheeled mobile robot being the best for hilly areas with super stability and traction control being its assets. It analyzes the different inputs from the information provided by the on-board sensor system for maneuvering. The robot has five degrees of freedom (DoF) providing it the flexibility to work in x and z axes as along with the standard pitch, roll and yaw directions.